Abstract Book: International Seminar of Lasers and Biomedical Photonics, LBMP 2023 : LBMP 2023 (Journal of Lasers in Medical Sciences, 2024)
International Seminar of Lasers and Biomedical Photonics, LBMP 2023 18-20 October 2023, Tehran, Iran Cooperated organization: Laser Application in Medical Sciences Research Center Medical Laser Research Center, Yara Institute, ACECR Co-operators: Amirkabir University of Technology Royan Institute, ACECR YARA Institute, ACECR Sharif University of Technology Laser and Plasma Research Institute, SBU Shahid Beheshti University of Medical Sciences Radiation Sciences Research Center, AJA University of Medical Sciences